Recomendações teórico-metodológicas para a publicação de dados bibliográficos abertos e conectados - Jesus, Ananda Fernanda de (2021)
The Web environment was designed to provide the sharing of information resources in digital format, however its original structure does not allow computational agents to understand the meaning of these resources, causing problems in the recovery process. Linked Open Data is a set of principles for publishing structured, connected data and available for reuse under an open license. Its adoption eases the problems of information retrieval on the Web and international libraries have already mobilized to publish their data according to these principles. In this sense it is questioned, how to publish Linked And Open Bibliographic Data? The objective was to analyze the process of publishing bibliographic data as Linked and Open Data in the light of the available scientific literature. A Systematic Literature Review and an empirical study of the institutions that published their data as Linked and Open Data was carried out. The results obtained were: (a) the mapping of the characteristics and specificities of the bibliographic data and its relationship with innovation and technologies; (b) the state of the art of the relationship between bibliographic data and Linked and Open Data; (c) evaluation of the cases of publication of bibliographic data in accordance with the 10 Best Practices for the publication of Linked and Open Data; (d) recommendations on the publication of Connected Open Bibliographic Data. It is concluded that the theoretical-methodological recommendations built in this research can act as a guide for the institutions that intend to start the process of publishing Linked and Open Data. In addition, there is a need to register institutions' decision making in a standardized manner during the Linked and Open Data publication process and that this process can be done based on the establishment of a policy for publishing bibliographic data such as Linked and Open Data. It is concluded that the established recommendations can serve as a starting point for the initiatives of the bibliographic universe that intend to publish their data as LOD.